Assessing Higher-Order Visual Processing in Cerebral Visual Impairment Using Naturalistic Virtual-Reality-Based Visual Search Tasks - Claire E. Manley; Christopher R. Bennett; Lotfi B. Merabet (Children, 2022)
Cerebral visual impairment (CVI) is a brain-based disorder associated with the maldevelopment of central visual pathways. Individuals with CVI often report difficulties with daily visual search tasks such as finding a favorite toy or familiar person in cluttered and crowded scenes. We developed two novel virtual reality (VR)-based visual search tasks combined with eye tracking to objectively assess higher order processing abilities in CVI. The first (virtual toybox) simulates a static object search, while the second (virtual hallway) represents a dynamic human search task. Participants were instructed to search for a preselected target while task demand was manipulated with respect to the presence of surrounding distractors. We found that CVI participants (when compared to age-matched controls) showed an overall impairment with visual search on both tasks and with respect to all gaze metrics. Furthermore, CVI participants showed a trend of worsening performance with increasing task demand. Finally, search performance was also impaired in CVI participants with normal/near normal visual acuity, suggesting that reduced stimulus visibility alone does not account for these observations. This novel approach may have important clinical utility in helping to assess environmental factors related to functional visual processing difficulties observed in CVI.